The impact of remote work on productivity in Sri Lanka's logistics and maritime sector - Nayanalochana, P.C.J.; Perera, U.N.S.R.; Kavindya, G.V.T. (University of Colombo, 2025)
This study investigates the impact of remote work on employee productivity in Sri Lanka's logistics and maritime sector, focusing on administrative, logistics management, and customer service roles at the Port of Colombo. While remote work has been extensively studied in knowledge-based sectors like IT, its effect on productivity in the maritime industry remains underexplored. Using an Ordinary Least Squares (OLS) multiple regression model, the research examines how work-life balance, communication effectiveness, work flexibility, and the physical work environment influence productivity in remote settings. The sample comprises 100 employees engaged in remote roles at Colombo Port, selected through purposive sampling. Data were collected via a structured questionnaire, measuring both independent variables and employee productivity using self-reported indicators such as task efficiency and job satisfaction. The regression analysis reveals that work-life balance, effective communication, and work flexibility all significantly contribute to productivity, with work-life balance showing the strongest effect, increasing productivity by 27%. Communication practices, with a coefficient of 0.220, also significantly enhance productivity by reducing errors and improving coordination in logistics and maritime operations. Work flexibility increases productivity by 23%, enabling employees to better manage personal and professional responsibilities. However, the physical work environment has a minimal, non-significant effect (12%) on productivity, highlighting that process efficiency and coordination are more critical in this sector. Demographic factors such as gender, age, experience, and salary also influence productivity, with female employees facing additional challenges due to domestic responsibilities. Age positively impacts productivity, especially for employees aged 26-35, whereas older employees over 36, often in management roles, experience a decline in productivity due to remote work challenges. The study concludes that understanding these factors is crucial for optimising remote work policies and addressing sector-specific challenges in Sri Lanka’s maritime industry.
Keywords: Remote working; Employee productivity; Maritime sector; Work-life balance; Logistics management